Land Subsidence Monitoring in Semarang and Demak Coastal Areas 2016-2017 Using Persistent Scatterer Interferometric Synthetic Aperture Radar. (August 2019) - Azeriansyah, R; Prasetyo, Y; Yuwono, B D
Abstract: Land subsidence is a problem faced in coastal areas of Java Island especially coastal areas of Semarang and Demak that caused by various natural and human factors. One method that can be used for this is by utilizing the method of Persistent Scatterer Interferometric Synthetic Aperture Radar (PS-InSAR). PS-InSAR is a remote sensing technique that is the development of the DInSAR method that can monitor the movement of the ground surface that allows users to perform regular measurements and monitoring of fixed objects on the surface of the earth. One of PS-InSAR method is Standford Method of Persistent Scatterers (StaMPS). StaMPS identify and extract the deformation signal even in the absence of bright scatterers. StaMPS is also applicable in areas undergoing non-steady deformation, with no prior knowledge of the variations in deformation rate. In addition, this method can also cover a large area. From the PS-InSAR method can be known the impact on the existing area in Semarang and Demak region per year from 2016 to 2017 by utilizing the image of Sentinel-1A. The result of PS-InSAR is done comparison of result from GNSS survey data.